Molecular Pathways and Therapeutic Advances in Ischemic Heart Diseases: Review Article (Journal of Pharma Insights and Research, 2025)
Ischemic heart disease (IHD) remains the predominant cause of global mortality, characterized by diminished cardiac blood supply and often complicated by ischemia-reperfusion injury during therapeutic interventions. While myocardial reperfusion is vital for restoring circulation, it paradoxically can amplify tissue damage. Recent scientific advances have illuminated multiple cardioprotective pathways that mitigate such injury. Notable among these are ischemic preconditioning and postconditioning, which activate crucial survival cascades including PI3K/Akt and MAPK pathways. Molecular mediators such as sirtuins, HIF-1α, and autophagy-related mechanisms play vital roles in maintaining mitochondrial function and diminishing oxidative stress. The interplay between reactive oxygen species and antioxidant defenses significantly influences cardiac injury outcomes. Pharmacological interventions, particularly statins, ACE inhibitors, beta-blockers, and antiplatelet agents, demonstrate substantial cardioprotective effects through their anti-inflammatory, anti-apoptotic, and endothelial-stabilizing properties. Emerging gene therapies target specific molecular pathways to enhance cardiac resilience. Non-pharmacological approaches, including structured exercise programs, Mediterranean dietary patterns, stress reduction techniques, smoking cessation, and weight management, have proven effective in preventing disease onset and progression. The successful prevention and treatment of IHD needs a combined approach of pharmacological interventions with lifestyle modifications